Manifestación de don Juan Lagarrigue a sus amigos sobre una solicitud de remoción - Lagarrigue, Juan (Establecimiento Tipográfico del Diario, 1856)
A collection of documents and correspondence compiled by Juan Lagarrigue in defense of his actions as administrator of the funds of the late Juan José Uribe.